Cardiovascular Disease and Its Implication for Higher Catastrophic Health Expenditures Among Households in Sub-Saharan Africa - Folashayo Ikenna Peter Adeniji; Taiwo Akinyode Obembe (Journal of Health Economics and Outcomes Research)
**Background:** Cardiovascular diseases (CVDs) impose an enormous and growing economic burden on households in sub-Saharan Africa (SSA). Like many chronic health conditions, CVD predisposes families to catastrophic health expenditure (CHE), especially in SSA due to the low health insurance coverage. This study assessed the impact of CVD on the risks of incurring higher CHE among households in Ghana and South Africa. **Methods:** The World Health Organization (WHO) Study on Global AGEing and Adult Health (WHO SAGE), Wave 1, implemented 2007-2010, was utilized. Following standard procedure, CHE was defined as the health expenditure above 5%, 10%, and 25% of total household expenditure. Similarly, a 40% threshold was applied to household total nonfood expenditure, also referred to as the capacity to pay. To compare the difference in mean CHE by household CVD status and the predictors of CHE, Student’s _t_-test and logistic regression were utilized. **Results:** The share of medical expenditure in total household spending was higher among households with CVD in Ghana and South Africa. Households with CVD were more likely to experience greater CHE across all the thresholds in Ghana. Households who reported having CVD were twice as likely to incur CHE at 5% threshold (odds ratio [OR], 1.946; confidence interval [CI], 0.965-1.095), 3 times as likely at 10% threshold (OR, 2.710; CI, 1.401-5.239), and 4 times more likely to experience CHE at both 25% and 40% thresholds, (OR, 3.696; CI, 0.956-14.286) and (OR, 4.107; CI, 1.908-8.841), respectively. In South Africa, households with CVD experienced higher CHE across all the thresholds examined compared with households without CVDs. However, only household CVD status, household health insurance status, and the presence of other disease conditions apart from CVD were associated with incurring CHE. Households who reported having CVD were 3 times more likely to incur CHE compared with households without CVD (OR, 3.002; CI, 1.013-8.902). **Conclusions:** Our findings suggest that CVD predisposed households to risk of higher CHE. Equity in health financing presupposes that access to health insurance should be predicated on individual health needs. Thus, targeting and prioritizing the health needs of individuals with regard to healthcare financing interventions in SSA is needed.